Biological evaluation of 7-O-amide hesperetin derivatives as multitarget-directed ligands for the treatment of Alzheimer's disease. (25th January 2021) - Wu, Mingfei; Zhu, Xingxing; Zhang, Yilong; Wang, Min; Liu, Tongtong; Han, Jianfei; Li, Jun; Li, Zeng
Abstract: A series of 7- O -amide hesperetin derivatives were subjected to multi-target biological evaluation of anti-Alzheimer's disease. Most of the compounds showed good in vitro inhibitory activity against cholinesterase, of which compound 7c (7- O -(4-(morpholinoethyl)-acetamide) hesperetin) was the most effective anti-eqBuChE derivative (IC50  = 0.28 ± 0.05 μM) and exerted neuroprotective effects. Further biological evaluation found that compounds 4d, 4e and 7c showed strong antioxidant, anti-Aβ self-aggregation and anti-neuroinflammatory activities. Compound 7c could inhibit the expression of iNOS and COX-2 proteins and prevent LPS-induced inflammatory response in BV2 cells. In addition, compound 7c could chelate biometal ions such as Cu 2+ and Zn 2+ . In the vivo study, the MWM test confirmed that compound 7c could improve the cognitive impairment caused by scopolamine. In summary, the above studies have shown that the optimized compound 7c has great development potential as MTDL for the treatment of AD. Highlights: Compound 7c displayed good inhibitory for BuChE and ROS formation. Compound 7c could prevent LPS-induced inflammatory response in BV2 cells. Compound 7c could chelate biometal ions such as Cu 2+ and Zn 2+ . The MWM test confirmed that compound 7c could improve the cognitive impairment.